Carbon paste electrodes modified with a reaction product obtained by hydrolysis of an antimony(III) salt - Švancara, Ivan; Florescu, Monica; Stočes, Matěj; Baldrianová, Lucie; Svobodová, Eva; Badea, Mihaela (Univerzita Pardubice, 2010)
In this article, a new type of antimony-modified electrode is described based on carbon-paste bulk dispersion of a precipitate obtained by hydrolysis of the respective Sb(III) salt. Subsequently, the resultant electrode (SbOL-CPE in two variants)  operated via the antimony film formed in nascenti at the electrode surface  was subjected to the basic characterisation with respect to its electroanalytical performance in the anodic stripping voltammetry of six heavy metal ions (Zn2+, Cd2+, Pb2+, Sn2+, In3+, and Tl+). As found out, the electrodes of interest have offered the behaviour and functioning comparable to the two related configurations of antimony film-plated (in situ) and antimony trioxide-modified carbon paste electrodes (SbFCPE and Sb2O3-CPE, respectively). Most importantly, the bulk modification with laboratory-prepared precipitate has been shown sufficiently reliable and the compound itself fairly reducible with stable behaviour; i.e., without need to refine or otherwise specially treat prior to use.
Keywords: carbon paste electrodes; hydrolysed antimony salt; bulk modification; antimony film; anodic stripping voltammetry; electroanalytical characterisation; heavy metals ions (Zn2+, Cd2+, Pb2+, Sn2+, In3+, and Tl+)